2019
DOI: 10.1186/s40104-019-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of age, weaning weight, body condition score, and reproductive tract score in pre-selected beef heifers relative to reproductive potential

Abstract: Background Artificial insemination is a preferred breeding method for beef heifers as it advances the genetic background, produces a predictive and profitable calving season, and extends the heifer’s reproductive life span. As reproductive efficiency in heifers is key for the success of beef cattle production systems, following artificial insemination, heifers are exposed to a bull for the remainder of the breeding season. Altogether, up to 95% of heifers might become pregnant in their first breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
0
24
0
4
Order By: Relevance
“…Heifer reproductive success in the first calving season is highly linked with lifetime reproductive efficiency [9][10][11]. A compilation of data from multiple studies demonstrated that first breeding season pregnancy rates in beef heifers range from 64 to 95% under natural breeding (NB) alone or the combination of artificial insemination (AI) followed by NB ( [12][13][14][15][16][17][18][19][20][21][22][23] (Fig. 1)).…”
Section: Importance Of First Breeding Season Success In Replacement Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Heifer reproductive success in the first calving season is highly linked with lifetime reproductive efficiency [9][10][11]. A compilation of data from multiple studies demonstrated that first breeding season pregnancy rates in beef heifers range from 64 to 95% under natural breeding (NB) alone or the combination of artificial insemination (AI) followed by NB ( [12][13][14][15][16][17][18][19][20][21][22][23] (Fig. 1)).…”
Section: Importance Of First Breeding Season Success In Replacement Hmentioning
confidence: 99%
“…By comparison, first service conception rates to artificial insemination are lower and range from 36% to 69% [12,14,17,18,20,21,23,24]. Our recent analysis of breeding records from 7 yrs (2011-2017) indicated that 43%, 42%, and 15% of heifers became pregnant by AI, NB, or failed to become pregnant during their first breeding season, respectively [23]. Under current production systems, the most efficient scenario occurs when replacement heifers conceive early in the breeding season.…”
Section: Importance Of First Breeding Season Success In Replacement Hmentioning
confidence: 99%
“…In industrial beef production setting, among reproductive targets are, age at first mating of 12 months [ 5 ], first calving time of 24 months of age, calving interval of 12 months, weaning rate of >95% of cows, and culling rate of lower than 5% of cows [ 6 ]. In practice, some modern beef farms reach an average first mating time at 13.7 months of age [ 7 ] and a calving interval of 13 months [ 8 ] while pregnancy rate can be varied from 53% to 95% under natural service or reduced to 48-69% when artificial insemination was utilized [ 7 ]. These figures indicate that there are opportunities to improve the productivity of beef cattle farming in the upland area of East Java.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is a common problem in humans and agriculturally important large mammals. For instance, prevalence of infertility may reach 16% 2 and 15% 3 in humans and beef female calves, respectively. Similar to what has been observed in humans 4 , the genetic architecture of fertility in beef heifers is very complex 5,6,7,8,9,10,11,12 .…”
Section: Introductionmentioning
confidence: 99%